L’avocat dans la procédure des anciennes coutumes médiévales bordelaises - Guyon, Gèrard D. (Cuadernos de Historia del Derecho, 2007)
The origins and functions of the lawyers who acted in the judicial scope of Bordeaux area during the Low Middle Ages, from the practice conserved in the old «coutumier» law of the zone; the author is focused in its presence and in the obligations picked up in this legislation, as well as in the ample role played by this law, more and more developed during that time.